Answer:
1/2
Step-by-step explanation:
Answer:
Step-by-step explanation:
To get the value of the expressions in list A and list B we will substitute y = 5 in each expression.
List A List B
1). 6 + 6y = 6 + 6(5) = 36 6y - 6 = 6(5) - 6 = 24
2). 6(y - 1) = 6(5 - 1) = 24 6(y + 1) = 6(5 + 1) = 36
3). 6y + 1 = 6(5) + 1 = 31 1 + 6y = 1 + 6(5) = 31
Therefore, (6 + 6y) is equivalent to 6(y + 1)
6(y - 1) is equivalent to (6y - 6)
(6y + 1) is equivalent to (1 + 6y)
Answer:
B) If you don't do you homework, then you can't go to the movies
Divide both sides of -105=-5g by -5. You'll get g = -105 / (-5), or g = 21.